Applying the theory of planned behaviour to hospitality management students in Nigeria: the mediating role of self-confidence. Issue 3 (17th September 2020) - Otache, Innocent
Abstract : Purpose: The purpose of this study is to explore the mediating role of self-confidence in the relationship between the constructs of the theory of planned behaviour (TPB) (i.e. attitudes towards behaviour [ATB], subjective norms [SN] and perceived behavioural control [PBC]) and the entrepreneurial intentions (EIs) of hospitality management students. Design/methodology/approach: This study adopted a quantitative approach. A self-reported questionnaire was used to collect data from a randomly selected sample of 126 hospitality management students from two federal polytechnics in Nigeria. To test the hypotheses formulated, partial least squares structural equation modelling was performed using SmartPLS software. Findings: The results indicated that ATB and PBC had significantly positive links with EIs. The link between SN and EIs was only positive but not statistically significant. Further analysis showed that self-confidence had a significantly positive link with EIs and mediated the relationships between ATB and EIs and between PBC and EIs. Practical implications: The findings have policy and practical implications for governments, policymakers and administrators of higher education institutions in Nigeria and other countries. Originality/value: To the author's best knowledge, this is the first study to provide empirical evidence of the mediating effect of self-confidence on the relationship between the TPB constructs and students' EIs. Theoretically, the findings of this study lend credence to the applicability of the TPB in predicting students' EIs across different contexts. More importantly, this study has modified the TPB by demonstrating that the effectiveness of the TPB constructs in influencing EIs depends on the degree of self-confidence that prospective entrepreneurs possess.